Innovations in conditioning and post-transplant maintenance in AML: genomically informed revelations on the graft-versus-leukemia effect - Murdock, H. Moses; Ho, Vincent T.; Garcia, Jacqueline S. (Frontiers in Immunology, 2024)
Acute Myeloid Leukemia (AML) is the prototype of cancer genomics as it was the first published cancer genome. Large-scale next generation/massively parallel sequencing efforts have identified recurrent alterations that inform prognosis and have guided the development of targeted therapies. Despite changes in the frontline and relapsed standard of care stemming from the success of small molecules targeting FLT3, IDH1/2, and apoptotic pathways, allogeneic stem cell transplantation (alloHSCT) and the resulting graft-versus-leukemia (GVL) effect remains the only curative option for most patients. Advances in conditioning regimens, graft-vs-host disease prophylaxis, anti-infective agents, and supportive care have made this modality feasible, reducing transplant related mortality even among patients with advanced age or medical comorbidities. As such, relapse has emerged now as the most common cause of transplant failure. Relapse may occur after alloHSCT because residual disease clones persist after transplant, and develop immune escape from GVL, or such clones may proliferate rapidly early after alloHSCT, and outpace donor immune reconstitution, leading to relapse before any GVL effect could set in. To address this issue, genomically informed therapies are increasingly being incorporated into pre-transplant conditioning, or as post-transplant maintenance or pre-emptive therapy in the setting of mixed/falling donor chimerism or persistent detectable measurable residual disease (MRD). There is an urgent need to better understand how these emerging therapies modulate the two sides of the GVHD vs. GVL coin: 1) how molecularly or immunologically targeted therapies affect engraftment, GVHD potential, and function of the donor graft and 2) how these therapies affect the immunogenicity and sensitivity of leukemic clones to the GVL effect. By maximizing the synergistic action of molecularly targeted agents, immunomodulating agents, conventional chemotherapy, and the GVL effect, there is hope for improving outcomes for patients with this often-devastating disease.